Rencana Strategis Teknologi Informasi pada PT XYZ dengan Kerangka Kerja Ward dan Peppard - Dicky Pratama; Derry Alamsyah (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2018)
Information technology is a much-needed asset in today's modern era. Not only as a tool as well as a core resource that should be utilized by organizations and companies. PT XYZ is one company that utilizes information technology to support its business process. Xi x hesitate in the procurement of the next information technology, given the cost that it requires. Companies are afraid of the investments made will be in vain because there is no appropriate information technology strategy to support its business processes. Therefore, it is necessary to make information technology strategy with company business strategy. This study was conducted with the work of Ward and Peppard. Before analyzing information technology strategy with SWOT Model Matrix previously performed internal and external environment analysis with Value Chain and PEST Analysis approach. The result of this research is the upcoming application portfolio which is expected to bring the competing superior company